Performance and environmental impact of biodegradable polymers as agricultural mulching films. (February 2016) - Touchaleaume, François; Martin-Closas, Lluís; Angellier-Coussy, Hélène; Chevillard, Anne; Cesar, Guy; Gontard, Nathalie; Gastaldi, Emmanuelle
Abstract: In the aim of resolving environmental key issues such as irreversible soil pollution by non-biodegradable and non-recoverable polyethylene (PE) fragments, a full-scale field experiment was set up to evaluate the suitability of four biodegradable materials based on poly(butylene adipate-co-terephtalate) (PBAT) to be used as sustainable alternatives to PE for mulching application in vineyard. Initial ultimate tensile properties, functional properties during field ageing (water vapour permeability and radiometric properties), biodegradability and agronomical performance of the mulched vines (wood production and fruiting yield) were studied. In spite of their early loss of physical integrity that occurred only five months after vine planting, the four materials satisfied all the requested functional properties and led to agronomic performance as high as polyethylene. In the light of the obtained results, the mulching material lifespan was questioned in the case of long-term perennial crop such as grapevine. Taking into account their mulching efficiency and biodegradability, the four PBAT-based studied materials are proven to constitute suitable alternatives to the excessively resistant PE material. Highlights: Assessment of in-use performances of PBAT-based films suitable for mulching. PBAT-based materials exhibit better radiometric properties than PE. PBAT-based mulch films lead to agronomical performance as high as PE. The early ageing of PBAT-based films is not detrimental to the vine performances. The material lifespan required for long-term crops mulching is questioned.